ICTs and development in India perspectives on the rural network society - Sreekumar, T. T. (India and Asia in the global economy., 2011)
"ICTs and development in India is a unique attempt to study the nature and consequences of the growing presence of information technology in development projects in India, focusing particularly on e-governance and information & communication technologies (ICT) development programs initiated by civil society organizations (CSOs). Sreekumar persuasively argues that there is in fact a wide chasm between the expectations and the actual benefits of CSO initiatives in rural India, and that recognising this crucial fact yields important lessons in conceptualizing development and social action in rural areas."--Publisher's description.